Hipermobilidade articular generalizada em indivíduos com disfunção temporomandibular - Pasinato, Fernanda (2010)
Temporomandibular dysfunction (TMD) include a variety of clinical problems that reach the temporomandibular joint, masticatory muscles and associated structures. Generalized joint hypermobility (GJH) has been reported as a predisposing factor for the occurrence of TMD. However, no consensus has been reached concerning this relation. This study aims to verify the incidence of GJH in individuals with TMD and asymptomatic individuals and their relation with clinical aspects and electrical activity of the masticatory muscles. 61 female volunteers were evaluated (34 individuals with TMD and 27 asymptomatic), with ages from 18 to 35 years, diagnosed with and without TMD by the Research Diagnosis Criteria for Temporomandibular Disorders (RDC/TMD). The participants were evaluated according to the presence of GJH through the Beighton Score. Electromyographic exams of the masseter and anterior temporal muscles were carried out, bilaterally, in mandibular rest, maximum intercuspal and mastication. A presence of 64.71% of GJH in individuals with TMD and 40.74% in the asymptomatic group was verified. A moderate positive correlation was observed between the GJH scores and the amplitude of passive mouth opening (p=0.0034), with pain (p=0.0029) and without pain (p=0.0081) in the TMD group. In this group, the individuals with GJH presented higher values of range of mandibular movement, except for protrusion. There was an opening mandibular range of movement with pain (p=0.0279) significantly higher in the group with TMD and GJH. Multiple diagnoses, according to RDC/TMD were present in most of the individuals with TMD. All subjects presented myofascial pain and 91.12% presented some joint impairment, especially arthralgia (79.41%). Disc disorders were present in 41% of the subjects. In the electromyographic evaluation, larger levels of resting electrical activity of temporal muscles were noted in relation to the masseters in individuals with TMD, with statistical significance for the left temporal muscle (p=0.0352). The volunteers with TMD and GJH presented larger values of RMS of the masticatory muscles in relation to individuals without hypermobility, with values in hyperactivity level for temporal muscles and statistical significance for the right masseter (p=0.0232) and left masseter (p=0.0129) muscles. In mastication, higher EMG activity was recorded in the control group, with significant difference for the right temporal muscle (p=0.0286). However, no significant difference was found regarding the presence of GJH. From these results, it can be concluded that individuals with TMD associated or not to GJH do not differ regarding the clinical aspects evaluated, except in relation to the mandibular opening range of movement. Electrical activity seems to have been influenced by GJH. The highest level of electrical activity observed in the subjects with GJH suggests that articular instability may lead to difficulties in the modulation of muscular contraction for the maintenance of the mandibular resting position.